Pola Komunikasi Keluarga Antara Menantu dan Mertua yang Tinggal dalam Satu Rumah - Elisabeth Saro; M. Abdul Ghofur; Amanah Rakhim Syahida (Unitri Press, 2019)
The study used qualitative research methods. The research is intended to know and understand in more detail related to the phenomenon of what is experienced by the subject to be investigated, through various data collection techniques conducted by researchers to obtain data on